Pekerjaan dalam Perspektif al-Qur’an: Studi Kasus Pekerja Disabilitas pada Konten YouTube - Helmalia; Faizah Binti Awad; Asliah Zainal; Nurdin; Muhammad Hasdin Has (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss work in the perspective of the Qur'an, case studies of disabled workers on Youtube content. So that no one else has a bad stigma against people with disabilities. This type of research is qualitative, by obtaining data sources from books of interpretation, YouTube content and other sources. One of the suras that discusses work is surah al-Mulk: 15. The interpretation of surah al-Mulk:15 explains that Allah SWT has made the earth easy for humans. So man's job is to travel all over to try to find sustenance. People with disabilities are able to work well when they manage time to develop themselves, have high enthusiasm and persistence to achieve their desires or goals. So, he can work like people in general who do not have disabilities.